The Relationship Of Mother's Knowledge And Husband's Support With Pregnant Women's Class Participation In The Working Area In The Petanang Health Center Area Lubuklinggau City In 2024 - Oktaviyantri, Oktaviyantri; Virgian, Kharisma; Eprila, Eprila (Journal of Maternal and Child Health Sciences (JMCHS), 2024)
Pregnant women's classes are an effort to reduce maternal mortality through examination activities and providing materials such as danger signs for pregnant women. However, many pregnant women do not participate in this activity, because they do not know about the class for pregnant women and their husbands do not support it. To find out the relationship between mother’s knowledge and husaband’s support with pregnant women’s class participation in the working area in the Petanang Health Center Area Lubuklinggau City in 2024. This study uses an analytical survey with a cross sectional research design. The sampling technique used accidental sampling with a sample of 44 respondents. The statistical test used in this study is the Chi-Square test and the significance value of mother’s knowlegde (ρ value 0.000) and husband’s support (ρ value 0.015). There is a relationship between mother’s knowledge and husband’s support with pregnant women’s class participation in the working area in the Petanang Health Center Area Lubuklinggau City in 2024